Clinical profile and outcome of acute kidney injury in preterm neonates in a level three neonatal intensive care unit - Gopalan, Divya; Hapani, Palak T. (International Journal of Contemporary Pediatrics, 2024)
Background: Acute kidney injury is an important cause of neonatal mortality and morbidity. Preterm neonates, in particular are a vulnerable population as they are associated with various risk factors, predisposing them to multi-organ injury. Data on AKI in preterm neonates in India are limited. There are several gaps including the risk factors, demographic profile and associations with other comorbidities which remain unanswered. The objectives of this study were to study the clinical profile, outcomes and various associated risk factors of AKI in preterm neonates. Methods: It is a prospective observational study conducted in neonatal intensive care unit of a government medical college hospital in Rajkot, Gujarat, India. 300 preterm neonates with AKI were selected and demographic details, risk factors associated with AKI and outcomes were studied. Results: It was found that among 300 newborns under study, 82% were males, 92% had sepsis, 65% had respiratory distress syndrome, 32% had birth asphyxia, 29% had shock, 30% had exposure to nephrotoxic drugs, 54% had requirement for mechanical ventilation, 94% patients were discharged and 6% patients expired. Conclusions: The most common risk factor associated with AKI was sepsis. The other important risk factors are birth asphyxia, respiratory distress syndrome, and shock. Monitoring of serum creatinine can help in early detection of acute kidney injury.